A house rabbit primer : understanding and caring for your companion rabbit - Moore, Lucile C., 1952- (Santa Monica Press LLC, 2022)
A House Rabbit Primer, 2nd Edition has been expanded to include more photos, new stories and care hints from experienced rabbit caretakers, and additional information on healthy rabbit diets. This new edition also features more detailed instructions on how to groom pet rabbits, as well as suggestions on how to care for special needs rabbits.